STUDI PENGUJIAN PARAMETER FISIS PADA DAUN PISANG KERING, DAUN JATI, DAN KULIT JAGUNG SEBAGAI WADAH MAKANAN - Fany Aliasra; Hernawati Hernawati; Muh. Said L. (JFT : Jurnal Fisika dan Terapannya, 2021)
This study aims to determine the physical quality of food containers made of dried banana leaves, teak leaves, and corn husks. The process of making a food container is carried out using a stainless steel mold which is then heated using a cooking thermometer to reach a temperature of 1000C and using a 10 kg load as a pressure, then printed for 5 minutes which is done 4 times printing for each food container. There are two tests for food containers, namely, the water absorption test, the average value of water absorption for food containers for dried banana leaves is 0.00%, 99,97% teak leaves, and 49.96% corn husks. The second test is test the resistance of the container based on temperature parameters. The temperatures used are 400C, 600C, and 800C, the three containers have different results, the dried banana leaf container can be used for hot food because it doesn't change after testing, while the food container made of leaves Teak and corn husk underwent changes during testing. Where teak leaves cannot be used for food with soup and corn husks cannot be used as food containers with food temperatures above 600 C.